The largest earthquakes in Algeria in the modern period: the El Asnam and Zemmouri-Boumerdès faults. - Bezzeghoud, Mourad (2019)
Algeria has experienced many destructive earthquakes during the last few centuries (e.g., Ayadi and Bezzeghoud, 2015). The city of El Asnam (formerly Orléanville, today Chlef) was severely damaged in 1954 and 1980 by magnitude 6.7 and 7.3 earthquakes, respectively. On October 10, 1989, a magnitude 5.9 earthquake struck the Mont Chenoua-Tipasa coastal area approximately 150 km west of Zemmouri, which is where the May 21, 2003 earthquake occurred (Mw6.8). Many other large historical and instrumental earthquakes have severely damaged the coastal cities of Algeria over the last few centuries (i.e., around Algiers, Oran, Mascara, Djidjelli, Constantine and Bejaia). These earthquakes suggest active deformation of the margin in conjunction with the clear offshore extent of active coastal faults. According to several studies, the main active geological structures around El Asnam, Algiers, Zemmouri and Boumerdès have experienced several disastrous earthquakes. Many other earthquakes have occurred in and around the Chlef and Mitidja Basins, underlining the seismic activity in the area. In this chapter, we highlight the main characteristics of the two largest earthquakes that have occurred in Algeria in the modern period: the El Asnam earthquakes of September 9 (Mw6.7) and October 10 1980 (Mw7.3), and the Zemmouri-Boumerdès earthquake of May 21, 2003, (Mw6.8).